FACTORS INFLUENCING THE ACHIEVEMENT OF PERSONAL SOCIAL DEVELOPMENT OF PRESCHOOL CHILDREN AT PEMBINA LIMBOTO STATE KINDERGARTEN - Piola, Wiwi Susanti; Sudirman, Andi Akifa; Blongkod, Ma'ratul Jannah (Jambura Nursing Journal, 2025)
Preschoolers experience a crucial developmental period filled with significant changes in various aspects of their lives. Social development in children is essential to pay attention to because it will impact how they socialize in later life, which is influenced by several factors. The purpose of this study was to determine the factors influencing the achievement of personal-social development in preschool-aged children. The research method used in this study was a quantitative analytical survey design with a cross-sectional approach. This study was conducted at Pembina Limboto State Kindergarten from September 2024 to January 2025. A sample of 56 respondents was taken using the cluster sampling technique, the number of samples was divided into 4 groups for each age representative. The results of the study showed that from the number of respondents as many as 56 preschool children, most common parenting style was the democratic category with 48 respondents (85.6%), authoritarian parenting with 4 respondents (7.1%), and permissive parenting with 4 respondents (7.1%). The most common peer group was the medium category with 36 respondents (64.3%), the high category with 15 respondents (28.6%), and low category with 4 respondents (7.1%). The most common growth and development stimulation was the good category with 52 respondents (92.9%), and the less category with 4 respondents (7.1%). The most common personal and social category was the normal category with 52 respondents (92.9%), and the suspect category with 4 respondents (7.1%). In conclusion, the most influential factor was growth and development stimulation, with a correlation of 0.731, which indicates a strong positive influence. This means that the better the growth and development stimulation a child receives, the more normal their personal and social development will be.